Seroprevalence of anti-SARS-CoV-2 IgG antibodies in Kenyan blood donors - Uyoga, S; Adetifa, IMO; Karanja, H; Nyagwange, J; Tuju, J; Wanjiku, P; Aman, R; Mwangangi, M; Amoth, P; Kasera, K; Ng’ang’a, W; Rombo, C; et al. (American Association for the Advancement of Science, 2021)
The spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Africa is poorly described. The first case of SARS-CoV-2 in Kenya was reported on 12 March 2020, and an overwhelming number of cases and deaths were expected, but by 31 July 2020, there were only 20,636 cases and 341 deaths. However, the extent of SARS-CoV-2 exposure in the community remains unknown. We determined the prevalence of anti–SARS-CoV-2 immunoglobulin G among blood donors in Kenya in April–June 2020. Crude seroprevalence was 5.6% (174 of 3098). Population-weighted, test-performance-adjusted national seroprevalence was 4.3% (95% confidence interval, 2.9 to 5.8%) and was highest in urban counties Mombasa (8.0%), Nairobi (7.3%), and Kisumu (5.5%). SARS-CoV-2 exposure is more extensive than indicated by case-based surveillance, and these results will help guide the pandemic response in Kenya and across Africa.